VIAGEM PARA LEMBRAR O ESQUECIMENTO DE UM POVO OU O DESATENTO ABANDONO DE SI (UM ESTUDO DE TERRA SONÂMBULA DE MIA COUTO) - Tutikian, Jane; da Silva, Vivian Ignes Albertoni (Organon, 2003)
The essay, based on Daniel-Henry Pageaux and Álvaro ManuelMachado theory, that distinguishes “trip literature” and “imaginative /static trip”, leads to the transgression of the traditional literature thathappened in the novel Terra Sonâmbula by Mia Couto, published in 1993.This transgression happens through the development of two narrative plans,in which the real objective is torn by the phenomenal manifestation of theAfrican reality introduction, getting apart from the epic speech throughthe present decay. Through the mythic consciousness and dream, the authorcontrasts the war and the destruction to the rescue of Mozambiqueidentity.